Benzo(a)pyrene induces oxidative stress, pro-inflammatory cytokines, expression of nuclear factor-kappa B and deregulation of wnt/beta- catenin signaling in colons of BALB/c mice201 (2016)
The incidence of colonic toxicity has been epidemiologically linked to the consumption of foods contaminated with benzo[a]pyrene (B[a]P). The present study investigated the effects of B[a]P on biomarkers of colonic stress, inflammation and Wnt/β-catenin signaling in colon of BALB/c mice. B[a]P was administered orally at 62.5, 125 and 250 mg/kg of B[a]P for 7 days by oral gavage. Exposure to B[a]P significantly decreased the colonic antioxidant enzyme activities and glutathione levels with concomitant significant increase in myeloperoxidase activity, nitric oxide and lipid peroxidation levels. Colon histopathology results showed treatment-related lesions characterized by atrophy, mucosal ulceration and gland erosion in the B[a]P-treated mice. Immunohistochemistry analysis showed that B[a]P treatment increased the protein expression of nuclear factor kappa B, pro-inflammatory cytokines namely tumor necrosis factor alpha and interleukin-1β, as well as cyclooxygenase-2 and inducible nitric oxide synthase in the mice colon. Altered canonical Wnt signaling was confirmed using diaminobenzidine staining for p38 mitogen activated protein kinase, β-catenin expression and absence of adenomatous polyposis coli following B[a]P administration. The present data highlight that exposure to B[a]P induces colonic injury via induction of oxidative and nitrosative stress, inflammatory biomarkers and dysregulation of Wnt/β-catenin signaling, thus confirming the role of B[a]P in the pathogenesis of colonic toxicity.